Storage protocol of dental pulp cells from human exfoliated deciduous teeth. - Lourenço Neto, Natalino; Pereira, Letícia Florindo; Marques, Nádia Carolina Teixeira; Prado, Mariel; Vitor, Luciana Lourenço Ribeiro; Tokuhara, Cintia Kazuko; Oliveira, Rodrigo Cardoso; Machado, Maria Aparecida Andrade Moreira; Oliveira, Thais Marchini (Brazilian Dental Science, 2017)
Objective: This study aimed to isolate the cells from the dental pulp tissue of human primary teeth, study the capacity of proliferation, characterize the cells and standardize the technique of culture and expansion to create a cell banking. Material and Methods: Primary teeth with no caries and orthodontic reasons were extracted for pulp tissue obtainment. The cells were extracted from the pulp cells, isolated and cultured under ideal conditions until full expansion. Results: After consecutive passages, the cultured cells were characterized using immunofluorescence technique and frozen between the 2nd and 6th passage, thus creating a biorepository of dental pulp cells from human primary teeth. Conclusion: The creation of a cell banking from dental pulp cells from human primary teeth enables the easy application of cells in laboratorial studies, reducing the cost and time for obtaining the samples, avoid the involvement of new subjects and allow a fast reproducibility of the researches. Keywords Cell culture techniques; Tooth, deciduous; Pulp; Fibroblasts; Cryopreservation.